DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS ULASAN CERPEN SISWA SD - Sutardi; Fitri Distrina Rahkmat; Mustofa (Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the implementation of the Discovery Learning approach in teaching short story review text writing to fifth-grade students at SD Negeri Mojo Kalitidu Bojonegoro. The study employed a qualitative descriptive method with fifth-grade students as the research subjects. Data were collected through observation, interviews, and documentation during the learning process. The results showed that the Discovery Learning approach was effective in improving students’ short story review writing skills. This was reflected in students’ active participation in listening to explanations, taking important notes, understanding the elements of review texts, as well as engaging in discussions and collaborating with peers. In addition, students were able to organize ideas, construct arguments, and write review texts using appropriate language within the allocated time. The effectiveness of the learning process was also indicated by the students’ average activity score of 85, categorized as very good, and an increase in learning performance by 63.16%. Therefore, the Discovery Learning approach is considered effective for teaching short story review text writing in elementary schools.